"Very much in love": The letters of Magda Arnold and Father John Gasson. Issue 3 (9th June 2017) - Rodkey, Elissa N.
Abstract: Magda Arnold (1903–2002), best known for her pioneering appraisal theory of emotion, belonged to the second generation of women in psychology who frequently experienced institutional sexism and career barriers. Following her religious conversion, Arnold had to contend with the additional challenge of being an openly Catholic woman in psychology at a time when Catholic academics were stigmatized. This paper announces the discovery of and relies upon a number of previously unknown primary sources on Magda Arnold, including approximately 150 letters exchanged by Arnold and Father John Gasson. This correspondence illuminates both the development of Arnold's thought and her navigation of the career challenges posed by her conversion. I argue that Gasson's emotional and intellectual support be considered as resources that helped Arnold succeed despite the discrimination she experienced. Given the romantic content of the correspondence, I also consider Arnold and Gasson in the context of other academic couples in psychology in this period and argue that religious belief ought to be further explored as a potential contributor to the resilience of women in psychology's history.